A polymorphism in histidine-rich calcium binding protein as second hit in phospholamban cardiomyopathy. (19th May 2022) - Van Der Voorn, SM; Dimitrova, K; Van Drie, E; Bourfiss, M; Taha, K; De Brouwer, R; Verstraelen, TE; De Boer, RA; Asselbergs, FW; Van Tintelen, JP; Van Veen, TAB
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Netherlands Cardio Vascular Research Initiative (CVON): the Dutch Heart Foundation, Dutch Federation of University Medical Center, the Netherlands Organization for Health Re-search and Development and the Royal Netherlands Academy of Sciences Introduction: Sudden cardiac death (SCD) is one of the severe manifestations in carriers with a phospholamban (PLN p.Arg14del) cardiomyopathy. Prediction whether a patient with this pathogenic variant will be at risk for SCD is difficult. PLN has an important role in cardiac calcium homeostasis as regulator of the sarcoplasmic reticulum (SR) Ca2+-ATPase (SERCA). It has been shown that the p.Arg14del pathogenic variant leads to Ca2+ overload in cardiomyocytes. Recently, it was found that dilated cardiomyopathy (DCM) patients who have a polymorphism in histidine-rich calcium binding protein (HRC Ser96Ala, rs3745297), displayed an increased risk for malignant arrhythmias and SCD. HRC resides within the SR, where it acts as a regulator of Ca2+ homeostasis. This Ser96Ala gene variant is widespread, as 60% of the general population bears at least one copy of this allele. Objective: To explore the effect of the HRC Ser96Ala polymorphism on ventricular arrhythmias and disease expression in PLN p.Arg14del pathogenic variant carriers. Methods: 337 p.Arg14del patients were included into the study; divided into wildtype (WT) (n=134, 24 index patients), heterozygous for Ser96Ala variant (n=142, 30 index patients) and homozygous for Ser96Ala variant (n=61, 11 index patients). The study was conducted according to the Declaration of Helsinki. Blood samples were genotyped on the Infinium® Global Screening Array-24 v3.0. Clinical data were subtracted from health records. Results: In total 23% of PLN variant carriers were diagnosed with DCM while 11% of the variant carriers were diagnosed with arrhythmogenic cardiomyopathy. A significant difference in age of presentation (p=0.019) of p.Arg14del patients diagnosed with a DCM phenotype was found in homozygous HRC variant carriers (median 43 years, [36-47.3], n=8) compared to WT (median 49 years, [41-56.8], n=24) and heterozygous variant carriers (median 58.5 years, [51-66.5], n=22). No significant differences between the 3 groups were detected in manifestations of premature ventricular contractions (n=188, p=0.203), non-sustained ventricular tachycardia (n=248, p=0.314) and appropriate ICD shocks (n=308, p=0.901). Conclusion: Although a significant difference in disease onset was found in PLN p.Arg14del patients with DCM who were homozygous for the HRC polymorphism, no correlations with arrhythmogenic parameters were found between patients with and without the HRC polymorphism. Therefore, we conclude that presence of the HRC polymorphism is not a discriminative predictor for arrhythmogenic events in PLN p.Arg14del.